The Public's Perception on Breast and Nipple Reconstruction: A Crowdsourcing-Based Assessment. (17th October 2018) - Azadgoli, Beina; Gould, Daniel J; Vartanian, Emma; Patel, Ketan M
Abstract: Background: Breast reconstruction outcomes have traditionally been measured by evaluating the opinions of patients and surgeons. Objectives: Our goal was to assess the views of the general public. Methods: A survey was designed and distributed through a crowdsourcing website called Amazon Mechanical Turk. Questions assessed participant demographics, personal experience with breast reconstruction, perceptions on breast reconstruction, and opinions regarding aesthetics results. Responses were analyzed using chi-square test. Results: A total of 992 responses were collected. Most participants were female (56.1%), white (32.1%), aged 30 to 39 years (40.4%), and had a bachelor's degree (42.0%). A total of 44.2% had personal experience with breast reconstruction and 25.8% with nipple reconstruction. Several aesthetic and reconstructive factors were significantly favored over others across sex, ethnicity, age group, education level, and personal experience with breast reconstruction. For instance, women were more likely to prefer reconstructed nipples ( P < 0.0001), view a breast without a nipple as complete ( P = 0.024) and place less importance on nipple shape ( P = 0.002). Additionally, those who personally experienced nipple reconstruction were willing to undergo more procedures for a complete nipple-areola complex ( P < 0.0001), to increase aesthetic results ( P = 0.018), and to increase chances of nipple survival ( P = 0.002). Conclusions: Crowdsourcing can be useful in plastic surgery and has helped identify several key findings. The importance of the nipple in reconstruction has been validated; almost three-quarters of respondents did not view a breast without a nipple as complete. The aesthetic preferences seem to support bilateral nipple-sparing reconstruction when possible. Most importantly, the respondents helped elucidate key differences in perception of aesthetic outcomes.